2013
DOI: 10.17221/91/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Migration flight of carrot psyllid (Trioza apicalis) at various latitudes is independent of local phenology

Abstract: A particularly advantageous method of monitoring the flight and calculating the median was used. An example is given in order to understand better the calculation. The medians show that the timing is similar at different latitudes despite local phenological differences. The difference in median flight times between Finland and the Czech Republic was five days on average, but phenological differences are about a month, shown by a comparison of temperatures, the monitoring of buds on spruce, and by the stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…However, adult psyllids were captured in horizontal green water traps several days prior to their detection in sweep net samples. These observations are in accordance with Láska (2013) [36], who indicated that water traps were suitable for capturing early immigrant psyllids. The maximum population movements of onion psyllids were detected using water traps around November, which correlated with their migration due to harvest.…”
Section: Discussionsupporting
confidence: 91%
“…However, adult psyllids were captured in horizontal green water traps several days prior to their detection in sweep net samples. These observations are in accordance with Láska (2013) [36], who indicated that water traps were suitable for capturing early immigrant psyllids. The maximum population movements of onion psyllids were detected using water traps around November, which correlated with their migration due to harvest.…”
Section: Discussionsupporting
confidence: 91%